Functional Traits Are Good Predictors of Tree Species Abundance Across 101 Subtropical Forest Species in China - Li, Ronghua; Zhu, Shidan; Lian, Juyu; Zhang, Hui; Liu, Hui; Ye, Wanhui; Ye, Qing (Frontiers in Plant Science, 2021)
What causes variation in species abundance for a given site remains a central question in community ecology. Foundational to trait-based ecology is the expectation that functional traits determine species abundance. However, the relative success of ecologists attempting to use functional traits to predict relative abundance is questionable. One reason for this is the diversity in plant function is greater than that characterized by few easily measured traits. Here, in a 200 000 m2 permanent mature subtropical forest plot (precipitation and nitrogen rich, light and phosphorus limited) in southern China, we analyzed the abundance of 101 woody plant species in relation to 12 easily and hardly measured traits. We found that: 1) leaf nitrogen content, leaf phosphorus content, specific leaf area, maximum CO2 assimilation rate, maximum stomata conductance, hydraulic conductivity, leaf water content and leaf turgor loss point significantly negatively associated with species abundance, 2) while leaf nitrogen content: leaf phosphorus content, wood density significantly positively correlated with species abundance; 3) no significant relationship was found between the stem xylem water potential at 50% loss of hydraulic conductivity and species abundance; 4) a combination of leaf nitrogen content, leaf phosphorus content, and maximum stomata conductance accounted for 45% of the variation in species abundance. Taken together, our findings suggested that the combination of the studied functional traits are powerful predictors of species abundance. Species with a resource-conservative strategy and invest more in constitutive tissue dominant in the mature forest.